Health determinants in urban China - Zhong Zhao (Institute for the Study of Labor (IZA), 2005)
This paper identifies health determinants in urban China applying Grossman model. Using wave of China Health and Nutrition Survey in 2000, we find that education has important positive effect on health, and cost of health care services has significantly negative impact. However, effects of wage rate and household income are insignificant. We also find that region is an important determinant of health. The body weight is also important, but unlike finding in developed countries, under-weight instead of over-weight is a better predictor for poor health. Our results suggest that male has better health than female does, and married couple has better health in urban China.
Keywords: I12; J24; D12; 330; self-reported health status; Grossman model; ordered probit; China